A new species of Eimeria (Apicomplexa: Eimeriidae) from Californian rabbits in Hebei Province, China. Issue 5 (October 2017) - Cui, Ping; Liu, Hongbin; Fang, Sufang; Gu, Xiaolong; Wang, Peng; Liu, Chunling; Tao, Geru; Liu, Xianyong; Suo, Xun
Abstract: Rabbit coccidiosis is caused by infection with one or usually several Eimeria species, parasitizing in hepatobiliary ducts or intestinal epithelium of rabbits. To date, 11 species of rabbit coccidia have been well documented. Here we report a new species of Eimeria from rabbits. Sporulated oocysts were ellipsoidal to slightly ovoidal, 37.4 (32.6–41.2) μm in length, 23.5 (20.9–25.5) μm in width, with a shape index (length/width) 1.6 (1.43–1.91) and smooth, bilayered, homogeneously thick wall. The micropyle was obvious and with an inner diameter of 6.2 (5.0–7.5) μm. Both oocyst residuum and polar granule were absent. Sporocysts were ellipsoidal to elongate, 17.2 (13.2–20.0) μm long and 8.4 (7.5–9.1) μm wide, with a shape index (length/width) of 2.1 (1.74–2.21) and the presence of Stieda body and sporocyst residuum. The prepatent period was 132 h. Phylogenetic analysis showed that 18S rDNA sequence of the new species clustered together with the 11 rabbit Eimeria species into a clade. However, ITS-1 sequence of the new species shared low similarities (27.1%–30%) with those of 11 rabbit Eimeria species. As the data above supported the erection of a new species, we named it as Eimeria kongi n. sp., in honor of Fanyao Kong, a Chinese parasitologist. The finding of the new species has important implications for the diagnosis and prevention of rabbit coccidiosis. Graphical abstract: Highlights: A new species of rabbit coccidia ( Eimeria ) is described. Eimeria kongi n. sp. resembles E. irresidua in size and shape. The prepatent period of the new species was 132 h, while E. irresidua was 216 h. Phylogenetic analyses of 18S and ITS-1 sequences supported the erection of the new species.